2012
DOI: 10.4093/dmj.2012.36.1.56
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Apolipoprotein A-II and Metabolic Syndrome in Korean Adults: A Comparison Study of Apolipoprotein A-I and Apolipoprotein B

Abstract: BackgroundApolipoprotein A-II (apoA-II) is the second-most abundant apolipoprotein in human high-density lipoprotein and its role in cardio metabolic risk is not entirely clear. It has been suggested to have poor anti-atherogenic or even pro-atherogenic properties, but there are few studies on the possible role of apoA-II in Asian populations. The aim of this study is to evaluate the role of apoA-II in metabolic syndrome (MetS) compared with apolipoprotein A-I (apoA-I) and apolipoprotein B (apoB) in Korean adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, the results of a current study showed that in vitro HDLs isolated from plasma of human apoA-II transgenic rabbits compared to normal rabbits had stronger activity for cholesterol efflux and stronger suppressive effects on inflammatory cytokines expression by macrophages (Wang et al, 2013). Also, in other studies, increased serum ApoA-II concentration has been introduced as a protective factor against CVD, hyperlipidemia, and metabolic syndrome (Birjmohun et al, 2007;Onat, G H, Ayhan, Ugur, & Can, 2009;Parra et al, 1992;Roselli della Rovere et al, 2003;Won Yi et al, 2012).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…However, the results of a current study showed that in vitro HDLs isolated from plasma of human apoA-II transgenic rabbits compared to normal rabbits had stronger activity for cholesterol efflux and stronger suppressive effects on inflammatory cytokines expression by macrophages (Wang et al, 2013). Also, in other studies, increased serum ApoA-II concentration has been introduced as a protective factor against CVD, hyperlipidemia, and metabolic syndrome (Birjmohun et al, 2007;Onat, G H, Ayhan, Ugur, & Can, 2009;Parra et al, 1992;Roselli della Rovere et al, 2003;Won Yi et al, 2012).…”
Section: Discussionmentioning
confidence: 51%
“…The results of human studies are also inconsistent. The results of some studies suggest that there is an inverse relationship between the serum level of ApoA-II and CRP (Birjmohun et al, 2007;Won Yi, Jeong, Lee, Son, & Kang, 2012) and CVD (Roselli della Rovere et al, 2003). In contrast, the results of a study showed that the risk of CAD was significantly lower in individuals with CC genotype than those carrying the T allele (Xiao et al, 2008).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In all other species, apoA-II is a monomer, does not contain a Cys residue, and thus does not form a heterodimer with apoA-I Milano ( 43 ). The low levels of circulating HDL-C in human carriers of apoA-I Milano may be related to an increased susceptibility of the apoA-I Milano -apoA-II heterodimer to proteolysis and increased clearance of apoA-II, which has been shown to be pro-atherogenic ( 42,44,45 ).…”
Section: A Peptide-based Approach To Hdl Therapymentioning
confidence: 99%
“…However, this association has not been found to be consistent in previous studies [22][23][24][25] although previous research suggested that ApoA1 affects glucose metabolism via multiple mechanisms, including enhanced insulin secretion [26], increased insulin-independent glucose uptake in muscle and adipose tissues [27,28], improved insulin sensitivity [29], and reversed adipocyte dysfunction [30] and restored adiponectin expression and insulin sensitivity [31] with ApoA1 mimetic peptide. Furthermore, genetic studies suggested that genetic variation in ABCA1 has been associated with the increased risk of T2DM [32], and one study suggested that loss-of-function mutations in ABCA1 were associated with impaired b-cell function, but not with the development of T2DM [33].…”
Section: Discussionmentioning
confidence: 44%